2015
DOI: 10.1063/1.4907245
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and dynamical topology properties of VANET based on complex networks theory

Abstract: Vehicular Ad hoc Network (VANET) is a special subset of multi-hop Mobile Ad hoc Networks in which vehicles can not only communicate with each other but also with the fixed equipments along the roads through wireless interfaces. Recently, it has been discovered that essential systems in real world share similar properties. When they are regarded as networks, among which the dynamic topology structure of VANET system is an important issue. Many real world networks are actually growing with preferential attachmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In [9] mobile phone users' trajectory proves that humans follow simple reproducible patterns. According to the research results in [10,17,18], VANET is a small world. In [19], a query processing algorithm that can determine the scope of each query is used to help vehicles to avoid returning overwhelmed large amount results.…”
Section: Discussionmentioning
confidence: 99%
“…In [9] mobile phone users' trajectory proves that humans follow simple reproducible patterns. According to the research results in [10,17,18], VANET is a small world. In [19], a query processing algorithm that can determine the scope of each query is used to help vehicles to avoid returning overwhelmed large amount results.…”
Section: Discussionmentioning
confidence: 99%
“…In the process of making an ordinary gypsum board, Zhang and Li directly mixed 21-22% commercial grade butyl stearate to make a phase change energy storage gypsum board wall and compared it with the ordinary gypsum board wall without adding phase change material. It is concluded that the physical and mechanical properties of the phase change gypsum board wall are better than those of the ordinary gypsum board wall, and its energy storage/releasing ability has been increased by ten times [6].…”
Section: Introductionmentioning
confidence: 98%
“…In the literature of vehicular networks, many researches focused on improvement of the vehicle mobility models [4], communication channel models and the routing strategies [5] [6], while the network properties as well as the complex characteristics of the vehicular networks have not been fully investigated. The vehicular networks are associated with a tremendous network size.…”
mentioning
confidence: 99%